Emergency surgical revascularisation for coronary angioplasty complications. Issue 5 (November 1994) - Carey, J A; Davies, S W; Balcon, R; Layton, C; Magee, P; Rothman, M T; Timmis, A D; Wright, J E; Walesby, R K
Abstract : OBJECTIVES--To evaluate trends in referrals for emergency operations after percutaneous transluminal coronary angioplasty (PTCA) complications; to analyse morbidity and mortality and assess the influence of PTCA backup on elective surgery. DESIGN--A retrospective analysis of patients requiring emergency surgical revascularisation within 24 hours of percutaneous transluminal coronary angioplasty. PATIENTS--Between January 1980 and December 1990, 75 patients requiring emergency surgery within 24 hours of percutaneous transluminal coronary angioplasty. SETTING--A tertiary referral centre and postgraduate teaching hospital. RESULTS--57 patients (76%) were men, the mean age was 55 (range 29-73) years, and 30 (40%) had had a previous myocardial infarction. Before PTCA, 68 (91%) had severe angina, 59 (79%) had multivessel disease, and six (8%) had a left ventricular ejection fraction of less than 40%. A mean of 2.1 grafts (range one to five) were performed; the internal mammary artery was used in only one patient. The operative mortality was 9% and inhospital mortality was 17%. There was a need for cardiac massage until bypass was established in 19 patients (25%): this was the most important outcome determinant (P = 0.0051) and was more common in those patients with multivessel disease (P = 0.0449) and in women (P = 0.0388). In 10 of the 19 cases a vacant operating theatre was unavailable, the operation being performed in the catheter laboratory or anaesthetic room. These 19 patients had an operative mortality of 32% and inhospital mortality of 47%, compared with 2% and 7% respectively for the 56 patients who awaited the next available operating theatre. Complications included myocardial infarction, 19 patients (25%); arrhythmias, 10 patients (3%); and gross neurological event, two patients (3%). The mean intensive care unit stay was 2.6 days (range 1 to 33 days) and the mean duration of hospital admission was 13 days (range 5-40 days). CONCLUSIONS--Patients undergoing emergency surgery after PTCA complications have a substantially increased inhospital mortality and morbidity. PTCA in this unit continues to require surgical cover. Delays in operating on stable patients in centres which operate a "next available theatre" backup policy may not differ from some units performing PTCA with offsite cover for PTCA complications. Particularly in the presence of multivessel disease, however, PTCA complications may be associated with the need for "crash" bypass and such patients are unlikely to survive hospital transfer. The proportion of patients requiring "crash" bypass has increased during the period reviewed because of the extent of disease in the emergency surgical group increased. These results indicate that surgery should not be denied to these patients.